2020
DOI: 10.34005/akademika.v9i02.1048
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Student Learning Anxiety Through Cyber Counseling-Based Individual Counseling Services

Abstract: There are two objectives of this study, to describe student learning anxiety before and after the intervention, and to find out whether or not cyber counseling-based individual counseling can reduce student learning anxiety. The research method used is quantitative research with experimental design. A total of 7 students are involved and asked in this study. Data collection was carried out by two methods, questionnaires and observation. There is two data analysis used, descriptive and inferential analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
1
0
3
Order By: Relevance
“…Penerapan teknologi non-Internet mungkin merata, tetapi teknologi Internet dinilai hanya di beberapa sekolah yang berada di perkotaan. Kemungkinan penggunaan teknologi khusus untuk konsultasi masih rendah, karena keahlian guru BK maupun aspek biaya (Haryati, 2020;Syam, 2020). Ada beberapa konselor kurang terampil dalam mengelola aplikasi-aplikasi teknologi komputer berbasis internet, kecuali jika konselor tersebut mau meluangkan waktunya secara konsisten untuk terus belajar atau mempunyai teman yang terampil dalam bidang teknologi sehingga dapat mendampingi dan berkerjasama agar bisa mempermudahkan, membantu dan memperluas pengetahuan dari konselor tersebut.…”
Section: Pandangan Aksiologi Cyber Counselingunclassified
“…Penerapan teknologi non-Internet mungkin merata, tetapi teknologi Internet dinilai hanya di beberapa sekolah yang berada di perkotaan. Kemungkinan penggunaan teknologi khusus untuk konsultasi masih rendah, karena keahlian guru BK maupun aspek biaya (Haryati, 2020;Syam, 2020). Ada beberapa konselor kurang terampil dalam mengelola aplikasi-aplikasi teknologi komputer berbasis internet, kecuali jika konselor tersebut mau meluangkan waktunya secara konsisten untuk terus belajar atau mempunyai teman yang terampil dalam bidang teknologi sehingga dapat mendampingi dan berkerjasama agar bisa mempermudahkan, membantu dan memperluas pengetahuan dari konselor tersebut.…”
Section: Pandangan Aksiologi Cyber Counselingunclassified
“…Multiculturalism in counseling has long been embedded across the curriculum and established as a subject known as multicultural training to develop counselor trainees' multicultural counseling competence to ensure they work effectively with diverse clients. Studies measuring counselors' multicultural counseling competence reported that the participants scored high (Aga Mohd Jaladin, 2017;Shah, 2019). However, there is an open question of whether these findings reflect the current generation of counselors.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…Hasil penelitian Syam (2020) tentang mereduksi kecemasan belajar siswa melalui konseling individu berbasis cybercounseling menemukan bahwa konseling individu melalui cybercounseling mampu menurunkan tingkat kecemasan belajar siswa yang sebelumnya ada pada kategori tinggi dan juga sangat tinggi menjadi sedang dan rendah. Dengan hasil tersebut, maka layanan konseling individu berbasis cybercounseling efektif dalam menurunkan kecemasan belajar pada siswa.…”
Section: Kerahasiaanunclassified